Clinical Guidelines for Dentistry in China During the Coronavirus Disease 2019 Pandemic - Luo, Wen; Wang, Jing; Tang, Maoxue; Peng, Jiaming; Ma, Wenmin; Wu, Yingying (Frontiers in Dental Medicine, 2021)
Preventing the spread of Coronavirus Disease 2019 (COVID-19) has become the focus of epidemiologists as the highly infectious respiratory disease spreads primarily by close, person-to-person contact via droplets or the skin. Aerosol dissemination may occur in a closed, high-aerosol environment. The aerosols generated in dental procedures can pollute surrounding air and device surfaces. In this paper, we summarize prevention and control measures relating to dentistry. We focus on the relationship between COVID-19 and dental disease prevention and control in dental treatment procedures and imaging examinations, oral health education and perspectives, and guidance for the practice of dentistry during the COVID-19 pandemic to provide a consistent and broadly endorsed standard for dental hospital and clinics.